Prevalence and risk factors of hypertension in rural Bangladesh: A population-based cross-sectional study - Sobiya Aziz Badat; C. Emdad Haque; Shakhawat Hossain; Alan Katz; Gias U. Ahsan (PLoS ONE, 2026)
Non-communicable diseases (NCDs), such as hypertension, are amongst the most fatal conditions afflicting people living in low- and middle-income countries (LMIC), including Bangladesh. This study addresses the lack of population-based studies in rural Bangladesh by examining the prevalence and distribution of hypertension and its associated risk factors. To this end, we surveyed adults aged ≥18 years (i.e., household heads and their spouses) from 7384 households across 149 villages in rural Bangladesh in 2017 using a semi-structured questionnaire to collect data on blood pressure, anthropometric, socioeconomic, lifestyle, and behavioral risk factors. Multivariate logistic regression analyses identified age, gender, and socioeconomic status as potential predictors of hypertension. The findings also showed that men and women from higher socioeconomic status (SES) groups had higher rates of overweight and obesity, risk factors for the development of hypertension (4.29% and 1.4% in adult men; 5.8% and 2.29% in adult women), as well as higher rates of fruit and vegetable consumption (10.29% and 7.25% in adult men; 9.95% and 6.84% in adult women). A significant association between tobacco consumption and age was observed for women (p=<0.0001), while higher levels of physical activity were found among men aged 45–54 years [OR:1.9, CI 95% (1.1–3.1)]. Furthermore, women in the highest SES brackets were 1.3 times as likely to engage in “moderate” physical activity as those in the lowest brackets. Age and overweight/obesity were found to be the strongest risk factors for hypertension in both genders, while education was not found to be significantly associated with hypertension in women. Notably, the findings revealed that 33.7% of men and 28.6% of women had elevated blood pressure, qualifying them as either prehypertensive or hypertensive. As such, we recommend that policy interventions aimed at stemming the growth of hypertension among Bangladesh’s rural populations should take gender-specific risk factors, rural-urban disparities, and socioeconomic context into serious policy consideration.